Dendrigraft polylysine coated‐poly(glycolic acid) fibrous scaffolds for hippocampal neurons. Issue 11 (8th July 2016) - Kojima, Chie; Fusaoka‐Nishioka, Eri; Imai, Toshio; Nakahira, Atsushi; Onodera, Hiroshi
Abstract: Poly(glycolic acid) (PGA) fibers are a good candidate material for nerve cell scaffolds, which is applicable to the treatment of peripheral nerve injuries. Polylysine is widely used as a coating material for cell substrates to promote nerve cell adhesion. In this study, linear and dendrigraft polylysines were used to coat PGA fibers. The association of large dendrigraft polylysines with PGA fibers was lower and unstable, compared with linear polylysine. However, more hippocampal neurons adhered to PGA fibers coated with large dendrigraft polylysine than linear polylysine. Enhanced cell adhesion was observed, even when the dendrigraft polylysine was coated on the PGA fibers at a low concentration (0.05 μg/mL) or when it was coated in water instead of alkaline buffer. Differences in cell adhesion properties were seen between the dendrigraft polylysine coating and a laminin coating. Thus, large dendrigraft polylysines are a useful coating material for nerve cell scaffolds. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 104A: 2744–2750, 2016.